2018
DOI: 10.1002/lt.25179
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine‐5'‐Diphosphocholine Protects the Liver From Ischemia/Reperfusion Injury Preserving Mitochondrial Function and Reducing Oxidative Stress

Abstract: Cytidine-5'-diphosphocholine (CDP-choline) participates as an intermediary in the synthesis of phosphatidylcholine, an essential component of cellular membranes. Citicoline treatment has shown beneficial effects in cerebral ischemia, but its potential to diminish reperfusion damage in liver has not been explored. In this work, we evaluated the hepatoprotective effect of citicoline and its possible association with inflammatory/oxidative stress and mitochondrial function because they are the main cellular featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
0
11
0
4
Order By: Relevance
“…The exact role each pathway contributes to the assembly and retention of hepatic TGs is not clear; however, the CDP-choline cycle is integrated into a larger metabolic network and interruption of the cycle might have a global impact on lipid-related metabolites in other pathways. CDP-choline can also protect against hypoxia and oxidative stress [82]. Thus, increased CDP-choline levels might represent a new biomarker to explain the retention of TGs in the fetal liver.…”
Section: Discussionmentioning
confidence: 99%
“…The exact role each pathway contributes to the assembly and retention of hepatic TGs is not clear; however, the CDP-choline cycle is integrated into a larger metabolic network and interruption of the cycle might have a global impact on lipid-related metabolites in other pathways. CDP-choline can also protect against hypoxia and oxidative stress [82]. Thus, increased CDP-choline levels might represent a new biomarker to explain the retention of TGs in the fetal liver.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the effect of miR‐449b‐5p in an in vivo rat model of hepatic I/R injury. It is well known that ALT (the specific marker for hepatic I/R injury) and AST (the nonspecific marker for hepatic injury) play important roles in hepatic I/R injury (Zazueta et al, ). In our study, both of these markers were significantly elevated in I/R rats, which is consistent with previous research (Torres‐González et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of phospholipid metabolism has not been specifically investigated in hepatic IRI, but PC administration has been shown to decrease intestinal IRI (42) and brain IRI (43). While Zazueta et al found CDP-choline to ameliorate IRI in non-steatotic liver, they did not evaluate effects in steatotic liver and did not measure lipid levels (44). Given the important role of PC as the predominant phospholipid in cell membranes, the relative decrease in PCs following IRI compared to non-steatotic livers may contribute to slower resolution of and recovery from IRI in steatotic liver.…”
Section: Discussionmentioning
confidence: 99%